-commuting maps and invariant approximations - Rhoades BE (SpringerOpen, 2006)
We obtain common fixed point results for generalized -nonexpansive -commuting maps. As applications, various best approximation results for this class of maps are derived in the setup of certain metrizable topological vector spaces.